Fuzzy multi-objective optimization model to design a sustainable closed-loop manufacturing system - Kousar, Sajida; Alvi, Asma; Kausar, Nasreen; Garg, Harish; Kadry, Seifedine; Kim, Jungeun (PEERJ INC, 2025)
Republicans and Democrats practically everywhere have been demonstrating concerns about environmental conservation to achieve sustainable development goals (SDGs) since the turn of the century. To promote fuel (energy) savings and a reduction in the amount of carbon dioxide CO2 emissions in several enterprises, actions have been taken based on the concepts described. This study proposes an environmentally friendly manufacturing system designed to minimize environmental impacts. Specifically, it aims to develop a sustainable manufacturing process that accounts for energy consumption and CO2 emissions from direct and indirect energy sources. A multi-objective mathematical model has been formulated, incorporating financial and environmental constraints, to minimize overall costs, energy consumption, and CO2 emissions within the manufacturing framework. The input model parameters for real-world situations are generally unpredictable, so a fuzzy multi-objective model will be developed as a way to handle it. The validity of the proposed ecological industrial design will be tested using a scenario-based approach. Results demonstrate the high reliability, applicability, and effectiveness of the proposed network when analyzed using the developed techniques.
Keywords: Multi-objective optimization; Closed-loop system; Sustainability; CHAIN NETWORK DESIGN; SUPPLY CHAIN; LOGISTICS; SELECTION; LOCATION; Computer Science